The Mughals and the Sufis : Islam and political imagination in India, 1500-1750 - Alam, Muzaffar, 1947- (State University of New York Press, 2021)
"Examines the relationship between Mughal political culture and the two dominant strains of Islam's Sufi traditions in South Asia: one centred around orthodoxy, the other focusing on a more accommodating and mystical spirituality"--